Revitalisasi Potensi Lokal melalui Pengembangan Sumber Daya Manusia dalam Mewujudkan Masyarakat yang Inovatif dan Kompetitif - Titis Ismail Saputro; Devita Haryanti; Enjelina Anzahri; Fitria Abeliya Istiqomah; Januari Rizki Lestari Nasution; Kurnia Febriani; Moulissa Ananda Vionica; Putri Aenna; Putri Liza Audina; Sri Rahayu Wulandari; Yandra Rivaldo; Muhammad Fadli Luran (CV. ALIM'SPUBLISHING, 2026)
Local potential is a strategic asset whose value depends on adaptive and innovative human resource development. This community service program aimed to strengthen local potential in the Kuliah Pengabdian Masyarakat (KPM) area through two integrated initiatives: digitalization and product photography training for Micro, Small, and Medium Enterprises (MSMEs), and a Creative Community School focused on public speaking and leadership for youth. Using a Participatory Action Research (PAR) approach, the program involved observation, socialization, training, mentoring, and evaluation, guided by human capital and community empowerment theories. Data were collected through observation, interviews, documentation, and literature review, then analyzed descriptively through data reduction, display, and conclusion drawing. The findings show improved participant understanding of digital marketing and product visual quality after the photography training, as well as increased awareness of communication and leadership skills among youth. These integrated programs demonstrate that human resource development effectively connects local economic potential with community innovation and competitiveness. The program offers a replicable, low-cost model for strengthening MSME marketing capacity and youth skill development based on local resources.